Practical Spreadsheet-Based Modelling for Effective Construction Project Scheduling - Kantianis, Dimitrios (Urban Planning and Construction, 2025)
Schedule and cost are traditionally considered critical factors in the effective management of construction projects. Particularly, the endemic conflicting relationship between duration and different types of cost and the need for optimal solutions is one of the most demanding problems for construction managers over time. Several commercial software packages along with open-source free to use applications are nowadays available to support project scheduling. However, these specialized software tools do not always seem to offer all the required optimization functions to facilitate the decision-making process, and a practical method is still required that could automatically produce optimal solutions, immediately answer “what-if” questions, and allow managers to conduct time-cost simulations. The paper initially displays the fundamental critical path network analysis and defines the problem of optimizing the project time-cost interrelation. Then, a spreadsheet-based formulation of a linear programming model to solve the time-cost trade-off problem is proposed and its flexible application to a medium-scale real construction project is analyzed. The work demonstrates that project planners in the construction industry can benefit immediately from easily derived rapid solutions at relatively low cost by changing the reference values of critical variables. It is also believed that this practical and automated optimization technique can contribute to the accomplishment of successful decision-making in construction project scheduling. Therefore, the paper aims at motivating construction managers to make more extensive application of spreadsheet modelling in conjunction with the built-in solving add-in algorithms to address complex time-cost trade-off relationships and, in general, to achieve more realistic project simulation and scheduling.